Citrus CsACD2 Is a Target of Candidatus Liberibacter Asiaticus in Huanglongbing Disease. Issue 2 (5th August 2020) - Pang, Zhiqian; Zhang, Li; Coaker, Gitta; Ma, Wenbo; He, Sheng-Yang; Wang, Nian
Abstract: Candidatus Liberibacter asiaticus targets citrus CsACD2 to promote devastating Huanglongbing disease. Abstract: Citrus Huanglongbing (HLB), caused by Candidatus Liberibacter asiaticus (Las), is one of the most destructive citrus diseases worldwide, yet how Las causes HLB is poorly understood. Here we show that a Las-secreted protein, SDE15 (CLIBASIA_04025), suppresses plant immunity and promotes Las multiplication. Transgenic expression of SDE15 in Duncan grapefruit ( Citrus × paradisi ) suppresses the hypersensitive response induced by Xanthomonas citri ssp. citri ( Xcc ) and reduces the expression of immunity-related genes. SDE15 also suppresses the hypersensitive response triggered by the Xanthomonas vesicatoria effector protein AvrBsT in Nicotiana benthamiana, suggesting that it may be a broad-spectrum suppressor of plant immunity. SDE15 interacts with the citrus protein CsACD2, a homolog of Arabidopsis ( Arabidopsis thaliana ) ACCELERATED CELL DEATH 2 (ACD2). SDE15 suppression of plant immunity is dependent on CsACD2, and overexpression of CsACD2 in citrus suppresses plant immunity and promotes Las multiplication, phenocopying overexpression of SDE15. Identification of CsACD2 as a susceptibility target has implications in genome editing for novel plant resistance against devastating HLB.